Decision Theory and Surgical Risk - Cattaneo, A. D.; Lucchelli, P. E.; Rocca, E. (Methods of Information in Medicine, 1974)
Reliability on the automatic prediction of the outcome in arterial reconstructive surgery was evaluated with the aid of a computer program based on decision theory. Twenty items of information were collected from 92 patients and used as predictors. Accuracy of the computerized allocation was checked by simple reclassification. Two risk functions, derived from two different loss matrices, were used to minimize the error probabilities.
Keywords: Decision Theory; Surgical Risk; Arteriosclerosis